2002
DOI: 10.1046/j.1440-0979.2002.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of postgraduate nursing students towards consumer participation in mental health services and the role of the consumer academic

Abstract: Consumer participation in health care is increasingly becoming an expectation of health services. While important progress has been made in the mental health area, the attitudes of mental health professionals towards consumers poses a severe limitation. Greater consumer involvement in the education of mental health professionals has been presented as a strategy to encourage the development of a greater acceptance of consumer involvement by health professionals. A consumer academic position has been introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 9 publications
6
78
2
Order By: Relevance
“…Additional research has examined mental health providers' willingness to empower patients (Hanse et al 2004;Happell et al 2002;Kent and Read 1998), as well as providers' attitudes toward involuntary commitment (Bowers et al 2003;Encandela et al 1999;Lepping et al 2004; Taylor, manuscript submitted for publication). The results from the current study are consistent with three themes that emerge from this literature: (1) there is some front-line provider resistance to sharing power with the patient; (2) providers' attitudes and values have some influence on their practice decisions; and (3) mental health providers often must choose between competing values when working with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has examined mental health providers' willingness to empower patients (Hanse et al 2004;Happell et al 2002;Kent and Read 1998), as well as providers' attitudes toward involuntary commitment (Bowers et al 2003;Encandela et al 1999;Lepping et al 2004; Taylor, manuscript submitted for publication). The results from the current study are consistent with three themes that emerge from this literature: (1) there is some front-line provider resistance to sharing power with the patient; (2) providers' attitudes and values have some influence on their practice decisions; and (3) mental health providers often must choose between competing values when working with clients.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The use of consumers as educators has largely been restricted to nursing and medical education, where their contribution has been reported to be well received. 36 Other reported advantages of using consumers are improved attitudes and a positive impact on nursing practices. 37,38 Although the benefits of pharmacists' membership in mental health advocacy organizations have been presented, 39 the research team did not retrieve any published reports of people with mental illnesses being previously employed in the continuing education of community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The use of mental health consumers as educators has been well received in nursing and medical education, especially in Australia. 24 A study demonstrating the potential value of consumer educators in the education of community pharmacists stated that use of consumer educators should be considered as a strategy for improving the confidence and communication skills of community pharmacists in providing pharmaceutical care for people with mental illnesses such as depression. 23,25 Meanwhile, several studies demonstrated that using consumer educators for pharmacy students reduced mental health stigma, 17,26 improved attitudes, and increased students' self-reported sense of empathy toward people with schizophrenia and depression, even on a long-term basis.…”
Section: Introductionmentioning
confidence: 99%